PROSES PEMBUATAN MESIN PENCACAH DAN PEMERAS LIDAH BUAYA UNTUK BAHAN DASAR KOSMETIK DENGAN KAPASITAS 30KG/JAM - Setiawan, Bagus; Sutrisno, Franky; NURDIANA, NURDIANA; Lubis, Zulkifli; Mahyunis, Mahyunis (MEKANIK: Jurnal Ilmiah Teknik Mesin, 2017)
Traditional tools used in Aloe vera squeeze are classified as ineffective if used in medium and large scale processing. While the use of aloe vera as a raw material for a product is quite large, it is necessary to use an aloe vera squeezer that is able to overcome and handle the problem. So with the statement above, a machine that is capable of carrying out the process of curing and squeezing aloe vera for cosmetic ingredients is 30 kg / hour. In the process of making aloe vera machines and squeezing equipment used such as sawing machines, manual plate machines, lathes, welding machines, drilling machines, grinding machines. In the process of making this machine there is the main component workmanship and the processing time, namely the machine frame made of 37 "L" st time profile 9, 52 hours, screw press shaft made of 35 minutes S35 C material, the counter blade is made of material S 35 C 18 minutes, screw press made of 36 minutes plate material, screw press tube made of steel pipe material 2; 25 hours, inlet funnel from gallvanis plate material 2; 15 hours, outlet funnel made of gallvaniss plate material 1 25 hours, the aloe vera water filter is made from plate 1, 30 hours, a counter knife made of steel plate 2, 30 hours. From the time of the engine design, the total manufacturing schedule was obtained as the effective time was 26.7 hours, if the machining was estimated at 70% or (0.70), the machining time would be 26.7: 0.70 = 38.7 hours. so the reality time (reality in the field) is 38.7 hours.